Principles and Applications of Ceramic Humidity Sensors - Mario Pelino; Carlo Cantalini; Marco Faccio (Active and Passive Electronic Components)
This paper presents a brief review of the state of the art in humidity and gas ceramic sensors R&D; it also describes the principle, fabrication and application of the humidity-sensitive Si-doped a-hematite (α-Fe2O3) sintered compacts. The humidity signal response is characterized by volt-amperometric and impedance spectroscopy techniques in the 0-97% relative humidity (RH) range. The response time of the sensor is evaluated by 0-60% RH variations. Experimental techniques used to measure the hysteresis, drift, and aging of the humidity setasor are presented and the results are discussed. The CO sensitivity is investigated by activating the sensor in the 350-450℃ temperature range. A humidity-meter prototype, based on the α-Fe2O3 ceramic compact is described, and its electronics and features are presented in this paper.